(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A maintenance Organization or HMO is a type of insurance provider that works with a network of physicians to give the benefactor under its coverage basic and supplemental health in times of need. On the other hand, Perception may relate to psychology because psychology is the study of behavior and mental processes, while perception is how we react to situations. In other words, our behavior towards that situation and, in some circumstances, specifically in teaching and non-teaching personnel, developed perceptions that may or may not reflect reality and, consequently, influence their value system. The purpose of this study is to know the perception of teaching and non-teaching personnel in Bestlink College of the Philippines on acquiring Health Maintenance Organization Benefits in terms of Financial Protection, their willingness, and the advantages they thought were most beneficial for them. From the results of this study, most of the respondents are Aged 24-30 years old, come with a lot of females and groups of non-teaching than teaching, and have 1-3 years of service. The perception of the said respondents in terms of financial protection is “Agree,” while in willingness, it is “Strongly agree.” The premium benefits of members increase over a longer period of being a member, which has the lowest weighted mean but the highest advantage based on the perception of teaching and non-teaching personnel. The researchers recommend that they should try to increase their employees' knowledge of HMO by sending a memo to each department with all of the information about HMO benefits. If employees purchase HMO, it is much better if they have access to broad coverage. Also, researchers recommend that it be made available to all employees and that they decide whether or not to acquire it. Aside from acquiring a Health Maintenance Organization, the Bestlink College of the Philippines must propose a wellness program to all teaching and non- teaching staff. Adding to that, they should offer other Health Maintenance Organization Providers the same or almost to the benefits of their current provider.